Prevention of Infectious Complications in Acute Pancreatitis - A. A. Kashintsev; A. A. Zavrajnov; N. Yu. Kokhanenko; V. Yu. Proutski; I. A. Solovyev; A. A. Nadeeva; M. V. Antipova; E. L. Belyaeva; O. V. Zaitsev; M. A. Ilyina; A. V. Koshkina; V. Yu. Podshivalov; et al. (Неотложная медицинская помощь)
AIM OF STUDY. The study was aimed to evaluate the effectiveness of treating acute pancreatitis by early enteral nutrition and selective introduction of nutritional mixtures directly into the initial sections of the jejunum, bypassing the duodenum.MATERIAL AND METHODS. A comprehensive treatment method for acute pancreatitis was developed based on the use of a pancreatoduodenal catheter. The method focuses on preventing intestinal failure syndrome by isolating the duodenum and preventing any liquid from entering it while ensuring the selective introduction of glucose-saline solutions and/or enteral nutritional mixtures directly into the initial sections of the jejunum. Several Russian clinics are currently conducting the research approved by local ethics committees. This article presents preliminary results from the data analysis. The study included moderate to severe forms (according to the 2012 Atlanta classification) of acute biliary pancreatitis without indications for endoscopic retrograde cholangiopancreatography, as well as alimentary-alcoholic pancreatitis. The first group of patients received standard therapy according to the 2020 clinical guidelines of the Russian Society of Surgeons. The second group received standard therapy combined with the new selective enteral nutrition method. The observation period lasted until the end of the hospital treatment, including five mandatory visits and a final visit to the physician. A follow-up survey was conducted three months or more after discharge to identify delayed episodes of acute pancreatitis complications, focusing on the incidence of infectious complications and surgical interventions.RESULTS. A total of 148 patients were treated. Patients were evenly distributed by etiology, gender, age, and body mass index. The analysis revealed that the number of patients with infectious complications decreased from 19.3% in the comparison group to 6.67% in the study group (p=0.041). The number of patients requiring surgical interventions was 5.0% in the study group compared to 19.3% in the comparison group (p=0.017).CONCLUSIONS. The study demonstrated that the use of the new method in the comprehensive treatment of acute pancreatitis, including early enteral feeding at the onset of the disease, may improve the course of the disease by reducing the incidence of infectious complications and the number of necessary surgical interventions.